A novel blood-sampling technique in lactating sows: The mammary vein route. (December 2019) - Scollo, A.; Bresciani, C.; Romano, G.; Tagliaferri, L.; Righi, F.; Parmigiani, E.; Mazzoni, C.
Highlights: Mammary vein access was convenient under field conditions because only one person was required. Because only one person was needed, the mammary vein route required less labour than the jugular vein route. The mammary vein route did not require restraint. Sows vocalised less when the mammary vein route was used than when the jugular vein route was used. Abstract: In the pig industry, labour efficiency and animal welfare have become two of the most important factors for achieving technical goals and farming competitiveness. Blood sampling is one of the most common sample-collecting techniques, but routine on-field blood collection can be very demanding for farm operators and the welfare of the animals, in particular for lactating sows. The aim of this study was to describe and investigate the mammary vein as a novel means of blood access in lactating sows that does not require coercive restraint. The study involved a total of 68 sows: 34 animals were sampled from the jugular vein (Group J) and the other 34 sows from the mammary vein (Group M). Labour time and indicators of the sow welfare (vocalizations during collection and serum cortisol concentration in the 30 min after the procedure) were collected from the two groups. The total amount of labour required, calculated as the time employed to perform blood collection multiplied by the number of operators involved in performing the technique (one for Group M and two for Group J, one for restraint and one for sampling), was significantly lower in Group M than Group J (Group M, 39.83 ± 29.45 s; Group J, 82.73 ± 55.34 s; P  < 0.001). Mean blood volume collected at T0 was 4.81 ± 2.00 mL and 4.84 ± 1.73 mL in Group J and Group M, respectively ( P  > 0.05). The percentage of sows that vocalized in Group M was less than in Group J (2.94% vs. 94.12%; P  < 0.001). Serum cortisol concentrations were not statistically different between the two groups ( P  > 0.05). The present study suggests greater efficiency in terms of saving labour time and reducing sow vocalization during blood collection with the use of mammary vein access compared with jugular vein access.